Mitachth La Shatich - Somech, Aya (Israel, 2011)
Maya Linik, 84, was born in Germany and immigrated to Israel. She had six sons. 40 years ago, the eldest of them died, and this loss has separated her from the world ever since. Through scenes from Maya's daily routine and her relationships with her sons, the film reveals, layer by layer, the family's trauma, and with it, Maya's unique character. The film questions the very meaning of motherhood and of relationships between parents and children.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films